HDL & LDL Status in Untreated Newly Detected Type 2 Diabetic Patients - Iqbal, Abu Tarek; Uddin, M Jalal; Salehuddin, Md; Murad, Hasan (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objective: The study was conducted with a view to find out HDL & LDL status in newly detected untreated Type II diabetic patients. Methods: Study was carried out on 116 (66 male & 50 female) newly diagnosed untreated type 2 diabetes patients aged 40 - 65 years and were selected randomly for study. Fifty (25 male & 25 female) non diabetic subjects aged 40 - 65 years were randomly selected as control. Results: LDL - C was significantly higher (P<.0001) and HDL -C was significantly lower (<.0001) in study group in comparison to control group.Conclusion: Dyslipidemia is commonly found in type - 2 diabetic patients. It is a risk factor for microvascular complications. So it should be controlled effectively. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22877 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 31-33